KONDISI LINGKUNGAN SOSIAL DAN PSIKOLOGI LANSIA DI PANTI SOSIAL HUSNUL KHOTIMAH PEKANBARU - Nurvi Santi Susanti; Nofri Hasrianto (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2021)
Elderly age is the final stage of development in the human life cycle (Maryam, 2011). Physical development may stop until adolescence, but psychological, social, and spiritual development will never stop (Jobans, 1994). Psychological disorders that are often experienced by the elderly in nursing homes include depression, anxiety disorders, sleep disorders, dementia, Alzheimer's, diagnostic syndromes and can result in dependence on others. This study aims to describe the social and psychological conditions of the elderly in the nursing home environment of Husnul Khotimah Pekanbaru. Descriptive survey research method, the research subjects were selected using the total sampling technique, the population was 70 elderly, while the sample was 35 elderly, with the criteria of exclusion and inclusion. Data collection using a questionnaire. Data analysis using descriptive analysis. The results showed that the social environment of the elderly was mostly 22 (63%) with sufficient category. The psychological condition of the elderly was mostly 34 (97%) with sufficient category. It can be concluded that the description of the social and psychological conditions of the elderly in the social care center Husnul Khotimah Pekanbaru with good results